A study into ward traffic - P. Hardcatle (AOSIS, 1982)
The study was undertaken in 1980 and was prompted by a need to highlight some of the problems associated with the ward milieu, both for patient care and for nurse teaching. Being associated at that time with the clinical teaching department the author was very interested in looking into the amount of traffic entering the ward area. It seemed that the ward sister had a very difficult task in providing a therapeutic environment for her patients, and that patient care was always being criticised with little thought to what was actually occurring in the ward.